Maiden Voyages : Eastern Indonesian Women on the Move - Williams, Catharina Purwani (Book collections on Project MUSE., 2007)
Emphasizes how travel situates Eastern Indonesian women at the intersection of ethnicity/place, class and gender politics. Investigates theoretical issues of travel within feminist geography frameworks. Field research focuses on contemporary rural women and was conducted mainly in parts of East Nusa Tenggara and while travelling on boats in the region.